2021
DOI: 10.3390/su13031074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Functional Strength Training on Functional Movement and Balance in Middle-Aged Adults

Abstract: Functional movement deficiencies cause falls and injuries in adults. Functional strength training (FST) is emerging as a new training method for athletes, middle-aged and older adults, to improve functional movement: The present study was conducted in order to investigate the effects of FST on balance and functional movement in healthy and independent middle-aged adults. The sample for this study consisted of 46 physically active individuals (24 female and 22 male). A total of 46 subjects were divided based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
4
11
0
Order By: Relevance
“…However, the higher likelihood of regular exercise at an older age could be the result of availability of time when people retire from jobs. Since functional strength training helps to reduce the risk of deficiency, policy makers could incorporate functional strength training into their future intervention programs [8]. For the marital status variables, our finding is consistent with Chung et al and Ruseski et al, who found no association between marital status and exercise [64,65].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the higher likelihood of regular exercise at an older age could be the result of availability of time when people retire from jobs. Since functional strength training helps to reduce the risk of deficiency, policy makers could incorporate functional strength training into their future intervention programs [8]. For the marital status variables, our finding is consistent with Chung et al and Ruseski et al, who found no association between marital status and exercise [64,65].…”
Section: Discussionsupporting
confidence: 91%
“…The results are somewhat consistent with the findings of Hickey and Mason [60]. We argue that the negative relationship is a result of functional movement deficiency, which causes difficulty in the daily lives of older people, such as when exercising [8,[61][62][63]. However, the higher likelihood of regular exercise at an older age could be the result of availability of time when people retire from jobs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In total, 20 studies were selected in this study, including 15 RCTs [ 8 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and 5 non-RCTs [ 45 , 46 , 47 , 48 , 49 ]. All were published between 2016 and 2022 as peer-reviewed articles or dissertations.…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the untrained populations’ FMS composite scores [ 8 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. …”
Section: Figurementioning
confidence: 99%